An organophotocatalytic late-stage N–CH3 oxidation of trialkylamines to N-formamides with O2 in continuous flow. Issue 7 (28th January 2022) - Mandigma, Mark John P.; Žurauskas, Jonas; MacGregor, Callum I.; Edwards, Lee J.; Shahin, Ahmed; d'Heureuse, Ludwig; Yip, Philip; Birch, David J. S.; Gruber, Thomas; Heilmann, Jörg; John, Matthew P.; Barham, Joshua P.
Abstract : An N–CH3 -selective trialkylamine oxidation to N -formamides is reported in continuous flow using gaseous O2 . A novel, enhanced-solubility dicyanoanthracene organophotocatalyst switched the photochemical mechanism from electron to energy transfer. Abstract : We report an organophotocatalytic, N–CH3 -selective oxidation of trialkylamines in continuous flow. Based on the 9, 10-dicyanoanthracene (DCA ) core, a new catalyst (DCAS ) was designed with solubilizing groups for flow processing. This allowed O2 to be harnessed as a sustainable oxidant for late-stage photocatalytic N–CH3 oxidations of complex natural products and active pharmaceutical ingredients bearing functional groups not tolerated by previous methods. The organophotocatalytic gas–liquid flow process affords cleaner reactions than in batch mode, in short residence times of 13.5 min and productivities of up to 0.65 g per day. Spectroscopic and computational mechanistic studies showed that catalyst derivatization not only enhanced solubility of the new catalyst compared to poorly-soluble DCA, but profoundly diverted the photocatalytic mechanism from singlet electron transfer (SET) reductive quenching with amines toward energy transfer (En T) with O2 .